The Effectiveness of Improving Students’ Listening Skill Through August Rush Movie (ELang | An English Language Education Journal, 2018)
The research paper is entitled “The Effectiveness of Improving Students’ Listening Skill through August Rush Movie” which are written to be submitted to English Education Study Program of FKIP of UNIBBA as a partial fulfillment of requirements for taking Sarjana Pendidikan Degree. The aim of this research is to find out whether or not the August Rush movie as media in improving listening skill of grade XI AKA 2 students at SMK 1 LPPM RI Majalaya is effective and the responses of the students when they learn English Listening through August Rush movie. This research was classified as pre experimental research. The main subjects of this research were 35 students of class XI AKA 2 at SMK 1 LPPM RI Majalaya. The approach of this study was quantitative. Listening tests were used as the instruments of eliciting the data. The actions implemented in this research were using August Rush movie, giving more explanation in English, making use of the LCD projector optimally, and providing activities that enabled the students to enrich their vocabulary. The results of the research showed that the use of August Rush movie in the English teaching and learning process was effective to improve the students’ listening skills. There was an increase in the means score from 49.43 in the pre-test to 62.28 in the post-test. The increase of the means from pre-test to post-test was significant, proved by the t-test result that t-observed is higher than t-table (7.060 > 2.032). There were some good improvements in some aspects such as their familiarity in listening to English words. Moreover, the August Rush movie successfully caught the students’ attention. As a result, they watched the movie carefully as well as they heard the audio.